Analisis Kuat Tekan Bebas Tanah Lempung Distabilisasi Pasir dan Semen - Anwar Muda (Anterior Jurnal, 2016)
The purpose of this study was to determine how much additional sand and cement on clay soil stabilization Bukit Rawi to the pavement. The results showed that after the addition of 16% sand with cement 2% the value of UCS rose to 1.63 kg/cm2 of initial conditions 0.41 kg/cm2. Then, the addition of cement 4% of the value of UCS also increased by 6.53 kg/cm2. On the addition of cement amounted to 6% the value of UCS will rise until 7.51 kg/cm2 and the addition of cement amounted to 8% the value increased to 12.08 UCS kg/cm2, and the addition of cement 10% the value increased to 13.06 UCS kg/cm2. Thus, with the addition of 16% sand and cement optimum 10% qualified technical foundation layer under the highway because of the value of UCS result 13.06 kg/cm2 > UCS 6 kg/cm2.